Stability of human serum albumin structure upon toxin uptake explored by small angle neutron scattering. (11th April 2018) - Yu, Shun; Kent, Ben; Jafta, Charl J.; Petzold, Albrecht; Radulescu, Aurel; Schuchardt, Mirjam; Tölle, Markus; van der Giet, Markus; Zidek, Walter; Ballauff, Matthias
Abstract: Possible denaturation or tertiary structural changes of the protein human serum albumin (HSA) upon adsorption of uremic toxin is investigated using small-angle neutron scattering (SANS). Calorimetric data in previous studies give proof of the binding between HSA and two classes of uremic toxins: i) small molecular weight and ii) middle molecular weight molecules. A representative polyelectrolyte of negative net charge is used as a model middle molecule and two molecules phenylacetic acid (PhAA) and indoxyl sulfate (IDS) represent the small molecular weight toxins. The present study find no proof of destabilization of the protein structure upon toxin uptake. Analyzing the structure factor of scattering intensities from high concentrated protein samples complexed with PhAA and IDS show that interaction between native and complexed HSA is also not altered. However, a small effect of the net charge of HSA is found in the case of urea modified proteins. Graphical abstract: Highlights: HSA remains stable during interaction with toxins. Calorimetric signals during toxin adsorption are due to adsorption effects. Physiological urea solutions do not induce a structural change of HSA.